Índice general de Estudios Internacionales, números 1 al 99 - Internacionales, Estudios (Estudios Internacionales, 1992)
On the occasion of completing 100 issues of the International Studies Journal of the University of Chile, on this occasion we have wanted to make a special publication that includes a general index of the journal. Produced jointly with the Library of the Institute of International Studies, this index has been classified chronologically, by authors, by descriptors and sequentially. The purpose of this last ordering is to be able to use the index of descriptors, since each article has been identified with a special number that is not necessarily correlative.